2014
DOI: 10.1089/dia.2013.0244
|View full text |Cite
|
Sign up to set email alerts
|

Glucokinase Gene Mutations (MODY 2) in Asian Indians

Abstract: This is the first study of MODY 2 mutations from India and confirms the importance of considering GCK gene mutation screening in patients with mild early-onset hyperglycemia who are negative for β-cell antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Until recently, genetic studies among individuals of Asian Indian origin related to MODY have been limited to the screening of HNF1A, HNF4A and GCK genes. 20,25,26 In the current study we have performed a comprehensive MODY genetic screening using next-generation sequencing. To the best of our knowledge, this Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, genetic studies among individuals of Asian Indian origin related to MODY have been limited to the screening of HNF1A, HNF4A and GCK genes. 20,25,26 In the current study we have performed a comprehensive MODY genetic screening using next-generation sequencing. To the best of our knowledge, this Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(52) However, when 49 children and adolescents from a study in Chennai, India with hyperglycemia were sequenced for GCK mutations, none were discovered, despite other case reports of GCK -MODY in Indian patients. (53) A recent study of MODY in India utilized next-generation sequencing to attain sequence data for 10 MODY genes, rather than only the 3 most common. (54) This study found potentially damaging variants in HNF4A , GCK , HNF1A , PDX1 , HNF1B , NEUROD1 , and PAX4 in 11 of 56 patients tested.…”
Section: Mody Epidemiology Studiesmentioning
confidence: 99%
“…Previous reports from our centre on other MODY subtypes, showed that among the clinically classified MODY patients 9.6% (9/96) had MODY3 (Radha et al., ), 3.4% (3/87) had MODY1 (Anuradha et al., ) and two of six patients with mild hyperglycemia had MODY2 mutations (Kanthimathi et al., ). In this study, we report that the prevalence of HNF1B gene mutations among a series of young diabetes subjects with renal abnormalities seen at our centre is about 10% (5/50).…”
Section: Discussionmentioning
confidence: 99%